Same Type of Comparatives, But with Different Syntax and Semantics - Hu, Yaqing (Proceedings of the Amsterdam Colloquium, 2024)
Twoaspects of Chinese adjectival bi-comparatives (bi-comparatives) remain underexplored. First, a critical morphosyntactic difference between bare (without differential phrases) and differential bi-comparatives (with differential phrases) is that the morpheme chu, literally meaning ‘beyond/exceed’, is exclusively licensed in the latter, but not in the former. Second, unlike their English counterparts, bi-comparatives do not freely allow measure phrases (MPs) as the standard of comparison. These observations suggest that degrees may be accessible in some constructions, but not in others. I propose that (i) bare bi-comparatives do not characterize an ordering of degrees, but a directed scale segment (Schwarzschild 2020); and (ii) differential bi-comparatives also characterize a directed segment, but it allows the mapping of the segment onto a degree specified by the differential phrase, a role fulfilled by chu (à la Wellwood 2015). Taken together, Chinese adjectival bi-comparatives may constitute a case where degrees are not encoded in the lexical semantics of gradable adjectives (GAs), but introduced via a functional morpheme (Wellwood 2015; Bochnak et al. 2020).